THE SOLVENT OPTIMIZATION IN METOPROLOL DERIVATIZATION REACTION WITH 1-FLUORO-2,4-DINITROBENZENE - Bekti Nugraheni; Sudibyo Martono; Sugiyanto Sugiyanto (Jurnal Inovasi Teknik Kimia, 2025)
Metoprolol, or 1-[4-(2-Methoxyethyl)phenoxy]-3-[(1-methylethyl)amino]-2-propanol, is a β1-adrenergic receptor antagonist that is often used to treat cardiovascular disorders such as hypertension, arrhythmia, and heart failure. Metoprolol has an A value of 1% 1cm = 52a in acid solution at a wavelength of 274 nm, where the molar absorptivity value (Ԑ) is 1390.48 L/(mol . cm) so that metoprolol gives weak absorption in the UV region (Ԑ ~ 1000 L/(mol . cm)). This study aims to optimize the solvent in the derivatization reaction of metoprolol with 1-fluoro-2,4-dinitrobenzene (FDNB). Under optimum conditions, the metoprolol reaction should form a derivatization product with FDNB. Metoprolol derivatization reactionin methanol solvent is optimal at pH 10.0 in borate buffer, with a warm-up at room temperature for 80 minutes. Analysis of metoprolol by High Performance Liquid Chromatography (HPLC) using a Chromolith RP-18e column (100 mm x 4.6 mm; 2 µm) and phase acetonitrile: buffer acetate (0.2 M, pH 3.0) = 70:30 with a flow rate of 1.0 ml/min. Separation of metoprolol-DNB occurs at a time retention of 7,856 minutes, with an analysis time of 10 minutes. Reaction-derivatization of metoprolol in methanol solvent; the optimum condition was pH 10.0. It was concluded that metoprolol in methanol solvent was more effective because the derivatization reaction with FDNB did not require heating. Optimizing the metoprolol content determination method using the FDNB solution derivatizer in acetonitrile showed that the optimal mobile phase was a mixture of acetonitrile and 0.2 M acetate buffer (30:70, pH 3.0), with a flow rate of 1.0 mL/minute.